1996
DOI: 10.1016/s1074-7613(00)80322-2
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of an ATP-Gated Ion Channel, P2X1, in Thymocyte Apoptosis

Abstract: In the immune system, apoptosis is involved in intrathymic elimination of self-reactive thymocytes and in peripheral T cell tolerance to exogenous antigens. Here, we describe the role in T cell apoptosis of P(2x1), a nonselective cation channel activated by ATP. P(2X1) molecules are up-regulated in thymocytes during dexamethasone-induced apoptosis, and antagonists to these receptors protect thymocytes from cell death. Moreover, P(2X1) mRNA and protein levels increase in thymocytes induced to die in vivo by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 47 publications
4
74
0
1
Order By: Relevance
“…In experiments reported by Chvatchko et al (1996), P2X 1 receptor expression was upregulated in thymocytes by apoptotic stimuli such as dexamethasone and SEB, a superantigen that ligates the T cell receptor. Furthermore, exogenous ATP caused apoptosis that was prevented by apyrase, an enzyme that degrades ATP.…”
Section: P2x Receptors and Cytotoxicity: A Laboratory Curiosity Or A mentioning
confidence: 95%
See 2 more Smart Citations
“…In experiments reported by Chvatchko et al (1996), P2X 1 receptor expression was upregulated in thymocytes by apoptotic stimuli such as dexamethasone and SEB, a superantigen that ligates the T cell receptor. Furthermore, exogenous ATP caused apoptosis that was prevented by apyrase, an enzyme that degrades ATP.…”
Section: P2x Receptors and Cytotoxicity: A Laboratory Curiosity Or A mentioning
confidence: 95%
“…This lead us to suggest that plasma membrane ATP-gated channels may form a new family of ion channels with different permeability and ion selectivity, but linked by the common property of causing cell death under conditions of sustained stimulation (Murgia et al, 1992b). Recent data have confirmed that immune cells susceptible to ATP-mediated cytotoxicity express either P2X 1 or P2X 7 or maybe both (Buell et al, 1996c;Chvatchko et al, 1996;Dubyak et al, 1996). There has been some discussion in the past about the possibility that some cytolytic effect could be mediated via P2Y receptors.…”
Section: P2x Receptors and Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…85 However, recent findings suggest that P2X receptor expression is not altered by dexamethasone treatment, that the P2X receptor agonist, ATP, does not induce apoptosis in thymocytes, and that P2X receptor antagonists do not block corticosteroid-induced apoptosis. 86 The potassium ion is also implicated in corticosteroidinduced apoptosis.…”
Section: Changes In Calcium and Potassium Homeostasismentioning
confidence: 99%
“…Moreover, ATP and P2X1 have been implicated in antigen-mediated thymocyte apoptosis or programmed cell death [20], which is a developmental response of CD4 + CD8 + thymocytes that have inappropriately high antigen receptor affinity. In fact, most CD4 + CD8 + thymocytes do not reach functional maturity, but rather die either by negative selection, a TCR-mediated process, or by neglect, which is a default response that occurs in the absence of positive or negative selection [21].…”
Section: Introductionmentioning
confidence: 99%